PENGEMBANGAN USAHA MIKRO DAN KECIL BERDASARKAN PEMETAAN MASALAH DALAM BERUSAHA DI DESA SAYANG KABUPATEN SUMEDANG - Susanti, Elisa; Kudus, Imanudin (Jurnal Dinamika Pengabdian, 2020)
One reason for business failure is due to lack of exploration problems. Therefore, it is important to identify the problem before developing the business. The purpose of this article is to describe the development of micro and small businesses based on mapping the problems in conducting business in Sayang Village of Sumedang Regency. Problem mapping in doing business is done through interviews, observations and questionnaires, the results of which are then written on a canvas map. Efforts in developing micro and small businesses are carried out based on the results of the mapping. There are four activities in developing micro and small businesses, with a combination of community education method and training method. The results of the mapping show that there are problems in conducting business in Sayang Village, namely: lack of skilled resources, several business actors do not have the desire to develop their businesses, problems in the production process, problems in the process of packaging and food security, capital problems, lack of expertise in business development, lack of networks and relationships, lack of marketing, many products do not yet have a PIRT license and halal logo, and Bumdes (village-owned business entity) is not well-managed. The efforts made in developing micro and small businesses in Sayang Village are: (1) entrepreneurship education, aimed at enhancing the spirit of entrepreneurship and knowledge regarding business processes; (2) capital education, regarding capital management from capital programs provided by the government; (3) food product packaging training, aims to make food more durable; (4) creation and information dissemination of a website to market products through desasayang.hydroweb.id. Evaluation results show that education and training are considered to be useful, increase knowledge, and become motivations in conducting business. There is an expectation from business people in Sayang Village that other education and training should be held more continuously.Keywords: Entrepreneurship, problems in conducting business, micro and small business development. ABSTRAKSalah satu alasan kegagalan usaha adalah karena kurangnya eksplorasi masalah. Sehingga sangat penting mengidentifikasi masalah sebelum pengembangan usaha. Tujuan dari penulisan artikel ini adalah menggambarkan pengembangan usaha mikro dan kecil berdasarkan pemetaan masalah dalam melakukan usaha di Desa Sayang Kabupaten Sumedang. Pemetaan masalah dalam berusaha dilakukan melalui wawancara, observasi dan kuisioner, yang selanjutnya dituangkan dalam peta kanvas. Upaya pengembangan usaha mikro dan kecil dilakukan berdasarkan hasil pemetaan tersebut. Terdapat empat kegiatan dalam pengembangan usaha mikro dan kecil, dengan kombinasi metode pendidikan masyarakat dan metode pelatihan. Hasil pemetaan menunjukkan terdapat masalah dalam berusaha di Desa Sayang yaitu: kekurangan sumber daya terampil, beberapa pelaku usaha tidak memiliki keinginan untuk mengembangkan usahanya, masalah dalam proses produksi, masalah dalam proses pengemasan dan ketahanan makanan, masalah permodalan, kurangnya keahlian dalam pengembangan bisnis, kurangnya jejaring dan relasi, kurangnya pemasaran, banyak produk belum memiliki ijin PIRT dan logo halal, dan Bumdes tidak berjalan dengan baik. Upaya yang dilakukan dalam pengembangan usaha mikro dan kecil di Desa Sayang adalah: (1) Pendidikan kewirausahaan, bertujuan untuk meningkatkan jiwa kewirausahaan dan pengetahuan mengenai mengenai proses bisnis; (2) Penyuluhan permodalan, mengenai pengelolaan modal dari program permodalan yang diberikan pemerintah (3) Pelatihan pengemasan produk makanan, bertujuan agar makanan lebih bertahan lama (4) Pembuatan dan sosialisasi website untuk memasarkan produk melalui desasayang.hydroweb.id. Hasil evaluasi menunjukkan bahwa pendidikan dan pelatihan dianggap sangat bermanfaat, menambah pengetahuan, dan menjadi motivasi dalam berusaha. Terdapat harapan dari pelaku usaha di Desa Sayang yaitu dilakukan pendidikan dan pelatihan lainnya dengan lebih kontinu.Kata kunci: Kewirausahaan, masalah dalam berusaha, pengembangan usaha mikro dan kecil.